2017
DOI: 10.1097/hnp.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stents

Abstract: Ureteral stents have an indispensable place in urology, and indications for their use are increasing. However, stents can affect their users' quality of life negatively because of complications and adverse effects. This descriptive research aimed to determine the effect of ureteral stenting on quality of life. The study sample consisted of 75 patients. Data were collected using a questionnaire form, the SF-36 Quality of Life Scale, and the International Prostate Symptom Score. Patients were interviewed twice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
10
2
Order By: Relevance
“…Postoperative stenting has become the most frequent cause of morbidity in ureteroscopic stone removal. Joshi et al [ 24 ] and Ucuzal et al [ 25 ] reported that patients with stents had undesirable consequences and a significantly negative impact on patients’ quality of life. Therefore, whether it is necessary to routinely insert a stent after ureteroscopy for ureteric calculi remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative stenting has become the most frequent cause of morbidity in ureteroscopic stone removal. Joshi et al [ 24 ] and Ucuzal et al [ 25 ] reported that patients with stents had undesirable consequences and a significantly negative impact on patients’ quality of life. Therefore, whether it is necessary to routinely insert a stent after ureteroscopy for ureteric calculi remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the literature, double-J ureteral catheterisation patients have reported complaints such as hematuria, frequent urination, dysuria, pain, migration, encrustation, detachment, urinary infection, insomnia and anxiety. 3,6,[8][9][10] A significant portion of double-J catheterised patients say that they experience pain, and that their job performance is affected. 9,11 In recent years, it has been emphasised that minor urological interventions can also harm sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…7 Previous studies have found that lower urinary tract symptoms emerge after catheter replacement, which causes psychological problems, such as anxiety and depression. 3,6,[8][9][10]18 These symptoms negatively affect patients' life quality 8,10,26 and sexual function. 14 The patients had a mild ED before placement, and they had moderate ED a month after the procedure (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Along with percutaneous nephrostomy, ureteral stenting is the main wide-using method for successful elimination of the upper urinary tract obstruction different etiology [ 1 , 2 ]. Long-term inserted ureteral stent as a foreign body inside of urinary tract is causing the symptoms of irritation that usually make a negative influence on quality of life in a patient [ 3 ]. Ureteral stents-related symptoms (USRs) are the common complications of ureteral stent indwelling and may occur in 80% patients or even more [ 4 ].…”
Section: Introductionmentioning
confidence: 99%